2008
DOI: 10.1016/j.yexcr.2008.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Mouse early oocytes are transiently polar: Three-dimensional and ultrastructural analysis

Abstract: The oocytes of many invertebrate and non-mammalian vertebrate species are not only asymmetrical but also polar in the distribution of organelles, localized RNAs and proteins, and the oocyte polarity dictates the patterning of the future embryo. Polarily located within the oocytes of many species is the Balbiani body (Bb), which in Xenopus is known to be associated with the germinal granules responsible for the determination of germ cell fate. In contrast, in mammals, it is widely believed that the patterning o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 39 publications
3
61
0
1
Order By: Relevance
“…However, in some oocytes, the centrosomes, normally positioned in the center of a Balbiani body (see Figs. 4, 5 and 8 in Kloc et al, [12]), were located outside of the Balbiani body, often in the vicinity of oocyte plasma membrane ( Fig. 3e and f).…”
Section: Nobox +/− Ovariesmentioning
confidence: 72%
See 2 more Smart Citations
“…However, in some oocytes, the centrosomes, normally positioned in the center of a Balbiani body (see Figs. 4, 5 and 8 in Kloc et al, [12]), were located outside of the Balbiani body, often in the vicinity of oocyte plasma membrane ( Fig. 3e and f).…”
Section: Nobox +/− Ovariesmentioning
confidence: 72%
“…Nobox deficiency in mice and perturbation of NOBOX homeodomain in women result in the premature ovarian failure (POF) syndrome characterized by postnatal oocyte loss and the replacement of follicles by fibrous tissue [1,2,6,8,10]. In mice, as in the majority of other animal species, mitotic divisions of primary oogonia, followed by incomplete cytokinesis, lead to the formation of germ cell cysts (nests, clusters) containing several oocytes connected by intercellular bridges [11][12][13]. Subsequently, the germ cell cysts break apart: somatic cells invade the cysts and separate and surround individual oocytes, resulting in the formation of individual ovarian follicles, which, in mammals, are called primordial follicles [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both species the asymmetry is related to the localization of the Golgi complexes. In mouse oocytes, the Golgi complexes are organized around a pair of centrioles (the centrosome) and constitute a specific structure called the Balbiani body (Pepling et al, 2007; Kloc et al, 2008). The 3D reconstruction of the distribution of organelles in mouse oocytes showed that the Balbiani body was always located near the intercellular bridge connecting sister oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It has generally been thought that the primary role of the Balbiani body is to provide precursor yolk material and other metabolic requirements for the oocyte [Guraya, 1976]. It has also been hypothesised that the Balbiani body plays a role in the selection of the healthiest mitochondria for the future zygote [Cox and Spradling, 2003] and that it is a component of a vegetal pole RNA transport pathway [Kloc et al, 2008].…”
Section: Introductionmentioning
confidence: 99%